"Increasing Demands and Competing Priorities": How Organizational Structure Affects Worker Well-Being in the Victim Services Field - McGlinchey, Diana; Roebuck, Benjamin S.; Sakauye, Pauline; Lalonde, Caël; Ferns, Alyssa; Killian, Kyle (Administration in social work, 2025)
This study examined the impact of organizational structure on worker well-being in victim services in Canada. With data collected from 915 survey respondents, 24 semi-structured interviews, and 19 focus group participants, we found that although there are many aspects that negatively affect worker well-being (e.g. lack of funding, inadequate compensation, understaffing, large caseloads), positive aspects helped ameliorate the negative (e.g. a positive team environment, support from supervisors, flexibility and autonomy within the position, and witnessing client resilience). Given the increases in workload and stress stemming from the COVID-19 pandemic, it is essential to understand the current landscape of worker well-being. Aspects of the job that are associated with increased satisfaction include workers' relationships to direct colleagues, working conditions, and relationship to direct supervisor. Aspects of the job that are associated with decreased satisfaction include limited chances of moving up in career, compensation, and how demanding the job is. Some factors are beyond the organization's control, but there are some that employers could easily implement: provide adequate support and guidance to staff; allow flexibility in scheduling, tasks, and work location; transparency about how decisions are made; include workers in decisions that affect them; provide opportunities for professional development; remind workers that they are valued and appreciated; and avoid neoliberal approaches to self-care.